Associations between seizures and MRI in patients with anti‐NMDAR encephalitis. (6th July 2020) - Ni, Guanzhong; Lin, Wanrong; Cai, Xiaodong; Qin, Jiaming; Feng, Li; Zhu, Shaofang; Zhou, Liemin; Chen, Ziyi
Abstract : Objectives: Seizures are a prominent feature of anti– N ‐methyl‐d ‐aspartate receptor (anti‐NMDAR) encephalitis. Nearly half of brain magnetic resonance image (MRI) results are abnormal. The aim of our study was to evaluate the associations between seizures and brain MRI results in patients with anti‐NMDAR encephalitis. Methods: Patients with anti‐NMDAR encephalitis were enrolled between January 2015 and December 2018. The patients included were divided into normal and abnormal MRI groups. Seizure outcomes and modified Rankin Scale scores at the 1‐year follow‐up were assessed. Seizure characteristics and outcomes were compared between groups. Results: Of 35 patients with anti‐NMDAR encephalitis, 28 patients (80%) had reported seizures in the acute phase. Patients with abnormal MRI findings more frequently had focal seizures than patients with normal MRI findings (72.7% vs 17.6%, P  < .01). The incidence of patients treated with 2 or more antiepileptic drugs was higher in the normal MRI group than in the abnormal MRI group (100% vs 45.4%, P  < .01). The onset‐immunotherapy time was shorter in the abnormal MRI group than in the normal MRI group ( P  < .05). There were no statistically significant differences in seizure outcomes between the normal and abnormal MRI groups ( P  > .05). Conclusions: Focal seizures were most common in patients with abnormal MRI lesions. In the acute stage of the disease, the abnormal MRI group was more likely than the normal MRI group to achieve seizure control. Abnormal MRI findings did not affect the overall good prognosis of patients with anti‐NMDAR encephalitis with seizures.